The Vacancy‐Induced Electronic Structure of the SrTiO3−δ Surface. (14th November 2018) - Cook, Seyoung; Dylla, Maxwell T.; Rosenberg, Richard A.; Mansley, Zachary R.; Snyder, G. Jeffrey; Marks, Laurence D.; Fong, Dillon D.
Abstract: The emergence of a 2D electron gas (2DEG) on the (001) surface of oxygen‐deficient strontium titanate (SrTiO3−δ ) is investigated. Using in situ soft X‐ray spectroscopy and effective mass modeling, a series of quantitative band diagrams are developed to describe the evolution of near‐surface and bulk carrier concentrations, downward band bending, and Fermi level along a lateral gradient of oxygen vacancies formed on SrTiO3−δ by direct‐current resistive heating under ultrahigh vacuum conditions. Electrons are accumulated over a 3 nm region near the surface, confined within a potential well with saturated 300 meV downward band bending. The relation between Fermi levels and carrier concentrations near the surface suggests the density of states near the surface is much lower than the bulk density of states, which is consistent with the quantum‐confined subbands of a 2DEG. The quantitative relationship between the surface and bulk electronic structures developed in this work provides a guide for precise engineering of the oxygen‐vacancy‐induced 2DEG in SrTiO3 . Abstract : Using in situ soft X‐ray spectroscopy and effective mass modeling, the 2D electron gas (2DEG) at the surface of SrTiO3 and the dependence of its electronic structure on oxygen vacancy concentration are investigated. It is found that the electrons are accumulated within a 3 nm region at the surface, with a density of states consistent with quantum‐confined subbands of a 2DEG.